2014
DOI: 10.1093/cercor/bhu097
|View full text |Cite
|
Sign up to set email alerts
|

Early Brain Activity Relates to Subsequent Brain Growth in Premature Infants

Abstract: Recent experimental studies have shown that early brain activity is crucial for neuronal survival and the development of brain networks; however, it has been challenging to assess its role in the developing human brain. We employed serial quantitative magnetic resonance imaging to measure the rate of growth in circumscribed brain tissues from preterm to term age, and compared it with measures of electroencephalographic (EEG) activity during the first postnatal days by 2 different methods. EEG metrics of functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 120 publications
(100 citation statements)
references
References 87 publications
4
96
0
Order By: Relevance
“…Despite these limitations, a relationship to later outcomes has been established (Hellström-Westas and Rosén 2005;Olischar et al 2004;Sisman et al 2005;Wikström et al 2012). These findings are compatible with the proposal that the total amount of brain activity is important for early brain health (see also (Benders et al 2014). …”
Section: Early Prediction Of Long-term Neurodevelopmentsupporting
confidence: 82%
See 4 more Smart Citations
“…Despite these limitations, a relationship to later outcomes has been established (Hellström-Westas and Rosén 2005;Olischar et al 2004;Sisman et al 2005;Wikström et al 2012). These findings are compatible with the proposal that the total amount of brain activity is important for early brain health (see also (Benders et al 2014). …”
Section: Early Prediction Of Long-term Neurodevelopmentsupporting
confidence: 82%
“…movement, respiration spikes, and amplifier noise). Recent studies have shown that more conventional quantification of burst occurrence (Benders et al 2014) and the presence of vigilance state cycling (a.k.a. sleep wake cycling; SWC) (Stevenson et al 2014) may inform brain health.…”
Section: Methodological Considerations and Future Directionsmentioning
confidence: 99%
See 3 more Smart Citations